Bible Study as Luminous Converting Encounter: Swiss Pietist Initiatives in 19th-Century French Canada. Issue 2 (November 2019) - Scorgie, Glen G.
This article examines the understanding and use of Scripture in the evangelistic endeavors of "awakened" pietistic francophone Swiss Protestant missionaries in 19th-century French Canada (after 1867, Quebec). It begins by sketching the roots of this transatlantic initiative in Le Réveil, the Continental francophone expression of the Second Evangelical Awakening. It then shows how within this movement historic Protestant Bible-centeredness converged with an intensified pietistic expectation that receptive contemplation of Scripture (especially in conversational settings) could evoke profoundly experiential and transforming encounters with the divine. The records of the Swiss missionaries also display a mystic-like apprehension of Scripture's luminosity, and of conversion as a comprehensively illuminating and radiant experience. This account challenges the assumption that mystical tendencies necessarily lead to privatized spirituality, while illustrating how a distinct form of evangelical spirituality stimulated missionary endeavor and shaped missionary practice.